Splatoon. Vol. 15 - Hinodeya, Sankichi; Turnage, Bryant (Hinodeya, Sankichi. Splatoon, 2022)
"Team Blue engages in their most complicated Turf War yet as they combat the Shadows, whose personalities are exact mirror reflections of Team Blue's own! The result of the challenge will determine the fate of Inkopolis Square!"--